Brazilian university students in Spain: motivations and decision factors (Educação e Pesquisa, 2022)
International mobility of students is a phenomenon of increasing importance in the higher education scenario. Over the last years, an increase of studies and investigations around this topic has been observed. This article presents the results of an exploratory study whose purpose was to analyze the motivations and decision factors in the process of mobility of Brazilian university students who chose Spain for their higher education. The methodology utilized was quantitative research, a 3-point Likert scale, with 216 students from the Brazilian academic community in Spain, spread across undergraduate, master, and doctoral courses, and the use of statistical data sources. Comparing previous studies in the relevant literature and the results of this study has demonstrated that factors as the institution´s academic level and prestige and forward-looking perspectives are coincidental in both. In fact, these factors are included among the most significant ones in almost all studies on international mobility and have also been highlighted by researchers, confirming the importance of these factors when making the decision of studying abroad. On the other hand, among the factors that come forward as the most relevant in the flow of Brazilian students towards Spain, standing out are the international experience, scholarships, the country´s image and culture, prestige and forward-looking perspectives, and the Spanish language.